IMPLIKATUR PERCAKAPAN DAN PEMAKNAAN SIMBOL (DALAM SERIAL ANAK UPIN IPIN eps. RAYA YANG MAKNA) - prapti wigati purwaningrum (LPPM Universitas Bina Sarana Informatika, 2017)
This tendency draws interest to find implicatures and symbol. This paper is using dialog script of Upin Ipin the series part Raya yang Makna. In this analysis the writer uses speech act theory by Searl, implicature theory by Grice, semiotic theory by Pierce. Based on the analysis the writer found some implicatures and symbols from ketupat and Idul Fitri card. we must always keep in touch by sending card in Idul Fitri and we just give it to someone who celebrate Idul Fitri. ketupat has many symbols such as the shape of ketupat is very complicated, it represents for our sins, the content of ketupat is white means our sins are already forgive. besides that the important value of this serial, shows us about togetherness. It describes from upin Ipin and their friends. Meimei is chinese and jarjit comes from India but they are invited by opah to come to her house and eat ketupat. Key words: speech act, implicature, symbol, upin ipin the series part: raya yang makna